Utility of Magnetic Resonance Imaging to Monitor Surgical Meshes: Correlating Imaging and Clinical Outcome of Patients Undergoing Inguinal Hernia Repair. Issue 7 (July 2015) - Hansen, Nienke Lynn; Ciritsis, Alexander; Otto, Jens; Busch, Daniel; Kuhl, Christiane K.; Kraemer, Nils Andreas
Abstract : Objectives: From a surgeon's point of view, meshes implanted for inguinal hernia repair should overlap the defect by 3 cm or more during implantation to avoid hernia recurrence secondary to mesh shrinkage. The use of magnetic resonance imaging (MRI)–visible meshes now offers the opportunity to noninvasively monitor whether a hernia is still covered sufficiently in the living patient. The purpose of this study was therefore to evaluate the efficacy of hernia repair after mesh implantation based on MRI findings (mesh coverage, visibility of hernia structures) and based on the patient's postoperative symptoms. Materials and Methods: In this prospective study approved by the ethics committee, 13 MRI-visible meshes were implanted in 10 patients (3 bilaterally) for inguinal hernia repair between March 2012 and January 2013. Senior visceral surgeons (>7 years of experience) implanted the meshes via laparoscopic transabdominal preperitoneal procedure. Magnetic resonance imaging was performed within 1 week and at 3 months after surgery at a 1.5-T system. Mesh position, deformation, and coverage of the hernia were visually assessed in consensus and rated on a 4-point semiquantitative scoring system. Distances of hernia center point to the mesh borders (overlap) were measured. Mesh position and hernia coverage postoperatively and at 3 months after implantation were correlated with the respective patients' clinical symptoms. Statistical analysis was performed using the Wilcoxon signed rank test. Results: Two of the 13 meshes presented with an atypical mesh configuration along the course of psoas muscle with a short medial overlap of less than 2 cm. Eleven of the 13 meshes exhibited a typical mesh configuration with lateral folding and initial overlap of more than 2 cm. Between baseline and 3 months' follow-up, average overlap decreased in the medial direction by −10% (3.75 cm vs 3.36 cm, P = 0.22), in the lateral direction by −20% (3.55 cm vs 2.82 cm, P = 0.01), in the superior direction by −2% (5.82 cm vs 5.72 cm, P = 0.55), and in the posterior direction by −19% (4.11 cm vs 3.34 cm, P = 0.01). Between baseline and 3 months' follow-up, mesh folding increased mildly in the medial direction, whereas no change was found in the other directions. Individual folds of the mesh were flexible over time, whereas the gross visual configuration and location of meshes did not change. Four of the 13 former hernia sites were mildly painful at follow-up, whereas 9 of the 13 were completely asymptomatic. No correlation between clinical symptoms and mesh position or hernia coverage was found. Conclusions: Our results suggest that the actual postoperative mesh position after release of laparoscopic pneumoperitoneum may deviate from its position during surgery. Gross mesh position and configuration differed between patients but did not change within a given patient over the observation period of 3 months after surgery. We did not find a correlation between clinical symptoms and mesh configuration or position. Shrinkage of meshes does occur, yet not as concentric process, but regionally variable, leading to a reduced hernia coverage of up to −20% in the lateral and posterior directions.